Immunomodulatory pathways regulate expression of a spliced FKBP51 isoform in lymphocytes of melanoma patients. (13th May 2015) - Romano, Simona; D'Angelillo, Anna; Staibano, Stefania; Simeone, Ester; D'Arrigo, Paolo; Ascierto, Paolo Antonio; Scalvenzi, Massimiliano; Mascolo, Massimo; Ilardi, Gennaro; Merolla, Francesco; Jovarauskaite, Egle; Romano, Maria Fiammetta
Summary FKBP51 (gene FKBP5) is an immunophilin capable of immunosuppression expressed in melanoma and lymphocytes. We found increased levels of a spliced FKBP5 variant in the PBMCs of 124 patients with melanoma. This variant encodes for an unknown isoform (FKBP51s). We hypothesized that FKBP51s resulted from tumour interaction with immune cells, through PDL‐1/PD‐1. To address this issue, we performed melanoma/PBMC cocultures. Furthermore, the immunohistochemistry of 76 melanoma specimens served to investigate whether FKBP51s stained tumour infiltrating lymphocytes. Our results showed that PBMCs expressed FKBP51s when cocultured with melanoma. Tumour PDL‐1 knockdown or anti‐PD‐1 reduced FKBP51s expression in cocultured PBMCs. IHC showed a strong FKBP51s signal in tumour infiltrating lymphocytes, and lymphocytes of the invasion front of the tumour, along with melanoma PDL‐1 expression. When overexpressed in melanoma, FKBP51s facilitated PDL‐1 expression on the cell surface. In conclusion, our study shows that FKBP51s marks the PBMCs of patients with melanoma and is exploited by the tumour to immunomodulate through PDL‐1.